Regulatory Framework of SITASYA in Manado Smart City: A Legal Analysis - Lentang, Fahrozy; Annas, Muhammad (Universitas Muhammadiyah Yogyakarta, 2025)
The research will discuss the SITASYA application based on Mayor Regulation Number 10 of 2018 concerning Manado Smart City. The purpose of the research is to provide an overview of the SITASYA application based on Mayor Regulation Number 10 of 2018 concerning Manado Smart City, and how the Mayor Regulation relates to the Principles of E-Government. The research method used is normative research and empirical research. The results of the research show that there is an inaccuracy between the arrangements contained in the Mayor's Regulation and the management of the SITASYA application that is carried out. And the Mayor's Regulation identifies the inability of the Regulation to fulfill E-Government Principles such as transparency, accessibility, and data security Keywords: E-Government, Sitasya, Smart City